Pengaruh Penggunaan Metode Diskusi Dan Motivasi Belajar Terhadap Hasil Belajar Siswa Kelas V SDN Sukamampir - Kulsum, Siti; Kusumastuti, Mimin Nurjhani; Rumanta, Maman (Nuansa Akademik: Jurnal Pembangunan Masyarakat, 2023)
The research method used is quasy experiment and 2x2 factorial design. The research sample was 82 students at SDN Sumampir. The instruments used are questionnaires and tests. The data analysis used is a two-way Anova test. The conclusions from this study are (1) there is an influence between student learning outcomes with the learning of the video-assisted discussion method and the poster-assisted discussion method; (2) there is an influence between students' learning motivation with the video-assisted discussion method and poster-assisted discussion method; 3) For students who have high motivation, their learning outcomes will be higher if taught using the video-assisted discussion method compared to the poster-assisted discussion method; (4) For students who have low motivation, their learning outcomes will not be higher if they are taught using the poster-assisted discussion method compared to the video-assisted discussion method; (5) There is an interaction effect between media and learning motivation on student learning outcomes.